2015
DOI: 10.1158/1940-6207.capr-14-0250
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting Product Standards for Carcinogens in Smokeless Tobacco Products

Abstract: Smokeless tobacco (ST) products sold in the U.S. vary significantly in yields of nicotine and tobacco-specific nitrosamines (TSNA). With the passage of the Family Smoking Prevention and Tobacco Control Act, the Food and Drug Administration now has the authority to establish product standards. However, limited data exist determining the relative roles of pattern of ST use versus constituent levels in the ST product in exposure of users to carcinogens. In this study, ST users of brands varying in nicotine and TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…Specifically, it has been reported that NNK and NNN nitrosamine biomarkers in the urine of smokeless tobacco users increased 32 and 12%, respectively, for every one-unit (μg/g wet wt) increase in NNK and NNN levels within their smokeless tobacco products (Hatsukami et al, 2015). In tobacco, bacteria have been identified that are capable of reducing nitrate to nitrite for the formation of TSNAs, including species of Bacillus , Staphylococcus , and Corynebacterium (Di Giacomo et al, 2007; Fisher et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been reported that NNK and NNN nitrosamine biomarkers in the urine of smokeless tobacco users increased 32 and 12%, respectively, for every one-unit (μg/g wet wt) increase in NNK and NNN levels within their smokeless tobacco products (Hatsukami et al, 2015). In tobacco, bacteria have been identified that are capable of reducing nitrate to nitrite for the formation of TSNAs, including species of Bacillus , Staphylococcus , and Corynebacterium (Di Giacomo et al, 2007; Fisher et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…13 Hatsukami et al recently reported the levels of TSNAs in U.S. moist snuff and snus products and demonstrated that exposure to TSNAs is dependent on TSNA levels and independent of pattern of use. 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…1–6 The most abundant and potent TSNA is 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). 7–11 The major metabolic pathway for NNK (Scheme 1) is carbonyl reduction to both the ( R )- and ( S )- enantiomers of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), 12, 13 which, like NNK, are very potent carcinogens in rodents.…”
Section: Introductionmentioning
confidence: 99%